The Influence of Survival-Safety Skills on Adolescents’ Involvement in Promiscuity and Premarital Sexual Behavior - Enik Nurkholidah; Fauziah Fauziah; Muhammad Naufal Luthfi; Amara Arsyisyah Faradita (Bulletin of Counseling and Psychotherapy, 2026)
Adolescence is a critical developmental stage characterized by increased vulnerability to risky social and sexual behaviors due to curiosity, peer influence, and limited self-regulation. This study investigates the influence of Survival-Safety Skills on adolescents’ involvement in promiscuity and premarital sexual behavior among students of SMK Negeri 1 Yogyakarta. Adolescents’ ability to maintain personal safety is recognized as a crucial protective factor against risky social and sexual behaviors. A quantitative correlational design was employed with a sample of 973 students selected through simple random sampling. Data were collected using the Survival-Safety Skills Scale and the Promiscuity and Premarital Sexual Behavior (PPSB) Scale, both of which demonstrated high reliability (α = 0.958 and α = 0.878, respectively). The findings showed that most students had high Survival-Safety Skills (83.86%) and low levels of engagement in risky behaviors (97.74%). Spearman’s correlation analysis revealed a significant negative relationship between Survival-Safety Skills and involvement in promiscuous and premarital sexual behaviors (r = -0.385; p < 0.01). The coefficient of determination (R² = 0.1482) indicated that Survival-Safety Skills explained 14.82% of the variance in such behaviors. These results emphasize the importance of strengthening adolescents’ personal safety and self-protection competencies through education, counseling, and collaboration between schools, families, and communities to prevent risky behaviors.